Are attitudes toward labeling nano products linked to attitudes toward GMO? Exploring a potential 'spillover' effect for attitudes toward controversial technologies. Issue 1 (2nd January 2019) - Akin, Heather; Yeo, Sara K.; Wirz, Christopher D.; Scheufele, Dietram A.; Brossard, Dominique; Xenos, Michael A.; Corley, Elizabeth A.
ABSTRACT: We present an analysis of how citizens form attitudes about labeling nanotechnology, building on previous work on the socio-cultural dynamics under publics' perceptions of risks and governance of emerging technologies. We examine whether individuals' views about labeling nanotechnology products are correlated with their attitudes about genetically modified organisms (GMOs), which we argue offers preliminary support for a 'spillover' effect, such that individuals may anchor their judgments about nanotechnology to their attitudes about the more publicized GMO issue. Using data from a representative sample of U.S. adults, we find that GMO risk perceptions are associated with support for labeling nano-enabled products, and evidence that publics' perceptions of GMOs' benefits moderate the extent that nanotechnology benefit perceptions guide these attitudes. A tendency to defer to scientific authority also affects the extent to which individuals use their GMO risk and benefit perceptions to make a judgment about labeling. We conclude by discussing the implications of a possible technology spillover effect for responsible and anticipatory regulation and policy for emerging technologies.